Flow- Injection Spectrophotometric Determination of some Sulpha Drugs via Oxidative Coupling with 4-Amino-N, N-diethylaniline. Application to Various Samples - Azeez, Yousif J. (Sulaimani Journal for Pure and Applied Sciences, 2009)
A flow injection spectrophotometric method is described for the determinaiton of sulphonamides in aqueous and biological samples. The method is based on the oxidative coupling reaction of 4-amino-N, N-diethylaniline with sulphonamide drugs in the presence of potassium dichromate as oxidizing agent. Intense violet, water soluble dye was obtained which has a maximum absorption at 550nm,. Linear calibration graphs were obtained for different sulphonamides with a molar absorpitivity of 4200-5270 l mol-1 cm-1 and a relative standard deviation less than 0.56%. The proposed method has proved to be highly sensitive (detection limit range 0.30-0.63 μg ml-1 sulphonamide) and accurate (recovery % was 98.2-101.2%). The nature of the coloured dye and its stability constant were determined. The method was applied successfully to the determination of sulphonamide drugs in pharmaceutical preparations, blood and urine samples.Keywords: FIA, Spectrophotometer 4-amino-N, N-diethylaniline